Targeted Therapies in Cancer - Colotta, Francesco (Springer, 2017)
Cancers share a restricted set of characteristics crucial to the tumor phenotype: proliferation in the absence of external growth stimuli, avoidance of apoptosis and no limits to replication, escape from external growth-suppressive forces and the immune response, an inflammatory micro-environment with new blood vessel formation, and an ability to invade normal tissues. In the last 20 years, the molecular determinants of these behaviors are becoming increasingly well understood. This has changed the current paradigm underlying the drug discovery process intended to identify novel therapies to fight cancer.In the past most efforts to identify novel therapies to cancer were focused on the empirical observation of natural or chemically synthesized molecules that inhibited cancer cell growth in vitro and/or in vivo. Most often, the molecular mechanisms underlying the observed anti-cancer activities of empirically discovered anti-cancer agents were discovered afterwards. Cornerstones of currently used chemotherapeutic armamentarium have been discovered according to this “ empiricism-based paradigm.”